Field-programmable gate array (FPGA) technologies for high performance instrumentation - Gazzano, Julio Daniel Dondo; Crespo, Maria Liz; Cicuttin, Andres; Calle, Fernando Rincon (Advances in computer and electrical engineering (ACEE) book series, 2016)
This book presents experimental and theoretical research on FPBA-based design and the development of virtual scientific instrumentation that can be used by a broad segment of scientists across a variety of research fields"--Provided by publisher